Analisis Rasio Keuangan Dalam Mengukur Kinerja PT. Adira Dinamika Multi Finance tbk - asnahwati, asnahwati (Komunitas Manajemen Kompetitif, 2016)
Abstract: Financial condition will reflect how the performance of the company . Assess the financial performance of the company's goal is to evaluate and improve the state perusahaannya.Untuk measure the financial performance of the company can use financial ratios such as liquidity , solvency , activity and profitability .The purpose of this study is : 1 ) To determine the performance of PT . Adira Multi Finance Tbk terms of liquidity ratios , 2 ) To determine the performance of PT . Adira Multi Finance Tbk terms of solvency ratios , 3 ) To determine the performance of PT . Adira Multi Finance Tbk in terms of the activity ratios and 4 ) To determine the performance of PT. Adira Multi Finance Tbk in terms of the profitability ratio.The analytical method used is the method of comparison is to compare the company's financial ratios with industry standard ratio norm. Based on the analysis of the data obtained it was concluded that : 1 ) The company's performance in terms of the last two year Quick Ratios, has decreased but is generally still above standard industry norms. Means the company still Ilikuit. 2 ) corporate performance in terms of the solvency ratio Debt to Equity Ratio in a state insolvabel, and in terms of Debt to Total Assets Ratio also insolvabel. 3 ) company performance in terms of the ratio of the activity under standard industry norm, so it is said company 's effective yet efficient in utilizing all its assets to finance consumer and 4 ) corporate performance in terms of profitability Economical ( ROA ) in the last two years decreased, although the first 2 years is still above the industry standard norm, while in terms of their own capital profitability ( ROE ) at 2 years terakir sharp decline and fall below the standard norm industi. Means the company has not been efficient and effective in generating income through all sources of funding available. Keywords: performance , liquidity , solvency , activity and profitability.